The cosmic-ray energy spectrum above 1016 eV measured with the LOFAR radboud air shower array - Thoudam, S.; Buitink, S.; Corstanje, A.; Enriquez, J. E.; Falcke, H.; Hörandel, Jörg R.; Nelles, Anna; Rachen, J. P.; Rossetto, L.; Schellart, P.; Scholten, O.; Ter Veen, S.; et al. (Proceedings of Science, 2015)
The LOFAR Radboud Air Shower Array (LORA) is an array of 20 plastic scintillation detectors installed in the center of the LOFAR radio telescope in the Netherlands to measure extensive air showers induced by cosmic rays in the Earth's atmosphere. The primary goals of LORA are to trigger the read-out of the LOFAR radio antennas to record radio signals from air showers, and to assist the reconstruction of air shower properties with LOFAR by providing basic air shower parameters, such as the position of the shower axis on the ground, the arrival direction and the energy of the incoming cosmic ray. In this paper, we describe the various steps involved in the energy reconstruction of air showers measured with LORA, and present the all-particle cosmicray energy spectrum above 1016 eV reconstructed for the two extreme scenarios: pure protons and iron nuclei.
CRIS-Team Scopus Importer:2023-08-15